THE ROLE OF THE GREEN ECONOMY IN ENSURING SUSTAINABLE DEVELOPMENT OF UZBEKISTAN’S ECONOMY - Buranbayeva Shoira Rustamovna (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: This study examines the evolution, principles, and stages of the green economy, highlighting its potential to supplant the brown economy and achieve sustainable development. Methods: By analyzing historical trends and global initiatives, the research investigates strategies such as reduced investments in harmful industries, carbon taxation, and financial incentives for sustainable practices, with a focus on European examples like biodiversity conservation and the circular economy. Results: Findings reveal that while the green economy promotes environmental stewardship and economic alignment, its success depends on addressing socio-political barriers and fostering global collaboration. Novelty: The study uniquely differentiates the green economy from the low-carbon economy, presenting it as a comprehensive framework that not only targets carbon neutrality but also prioritizes social equity and long-term ecological stability.